The Epidemic Of The Metabolic Syndrome Among The Palestinians In The Gaza Strip - Jamee AS (Dove Medical Press, 2019)
Amal Shahwan Jamee,1–3 Victor Aboyans,1,2,4 Julien Magne,1,2,4 Pierre Marie Preux,1,2 Philippe Lacroix1,2,51Tropical Neuroepidemiology, Inserm UMR 1094, Limoges, France; 2School of Medicine, Institute of Neuroepidemiology and Tropical Neurology, CNRS FR 3503 GEIST, University of Limoges, Limoges, France; 3Department of Cardiology, Ministry of Health, Palestine; 4Department of Cardiology, Dupuytren University Hospital, Limoges, France; 5Department of Thoracic and Vascular Surgery – Vascular Medicine, Dupuytren University Hospital, Limoges, FranceCorrespondence: Amal Shahwan JameeSchool of Medicine, Institute of Neuroepidemiology and Tropical Neurology, University of Limoges, 2 rue du Dr Marcland, Limoges 87025, FranceTel +33754139112Email dr_amal08@yahoo.frBackground: The metabolic syndrome (MetS) is a major public health and clinical challenge worldwide. However, limited data are available in the Gaza strip. This study was undertaken to evaluate the prevalence of MetS and its association with atherosclerotic risk factors and cardiovascular diseases among Gazan adults’ community.Methods: A cross-sectional study was conducted in 2017, among all adults ≥25 years of age. Participants were selected by stratified cluster sampling method, in five governorates (urban, camps and rural) of Gaza strip. Questionnaires on socioeconomic status, lifestyle and cardiovascular risk factors were completed for 2107 participants. The cardiovascular diseases included clinical history of coronary artery disease (CAD), Lower extremity artery disease (LEAD diagnosed as ankle brachial index < 0.90) and history of stroke. MetS was defined based on the International Diabetes Federation criteria (IDF).Results: Among participants, 864 (41%) fulfilled the definition of MetS higher in females than males (50% vs 39%). In both genders, MetS prevalence increased significantly with age (p<0.001). Subjects with MetS were more obese (73.0% vs 29.4%), hypertensive (49.9% vs 13.0%), diabetic (36.8% vs 5.8%) and had more often low physical activity (58.1% vs 41.3%). Additionally, lipids profiles disorders were more prevalent in cases with MetS. We found MetS significantly associated with all cardiovascular conditions with odd-ratio (95% CI) respectively at 2.4 (95% CI 1.8–3.4) for CAD, 1.5 (95% CI1.1–1.9) for LEAD and 2.1 (95% CI 1.3–3.5) for stroke.Conclusion: The MetS is highly prevalent in the Palestinian population, particularly among women. Subjects with MetS are at significantly elevated risk for cardiovascular diseases.Keywords: metabolic syndrome, risk factors, cardiovascular disease, Palestine